Comparison of performance in physiology subject assessed by short essay type questions and multiple choice questions of first year medical students - Kumar, Pradeep; Ghildiyal, JP; Rajpoot, Ravindra Singh; Kumar, Sanjeev (Asian Journal of Medical Sciences, 2017)
Background: Assessment and evaluation in the curriculum of medical education plays an important role to enhance the learning ability of medical students and should provide the level of actual performance as well as the capacity to improve overall performance. Aims and Objectives: In the present study, the performance of medical students in Physiology was assessed by conventional type short essay questions (SEQ) and multiple choice questions (MCQ). Materials and Methods: This prospective (observational) study was conducted in the subject of Physiology, A total of 380 samples were taken from students enrolled for the 1st year medical curriculum in year 2013 to 2015. The subjects were divided in two groups: subjects of this group-I was assessed with two theory papers consist of short essay question (SEQ), practical exam without OSPE. The subjects of group-II were assessed their theory part only by MCQs and maximum part of practical exam by objective structured practical examination (OSPE). Results: The theory performance was significantly higher (p<0.05) in group-II students assessed by totally MCQ based two system tests and one terminal exams as compared to conventional type (SEQ). While the marks obtained in practical was assesses by six lab leaving tests, one terminal practical exam (OSPE) was also significantly high (p<0.005) as compared to group-I. Our data showed that the performance of two problem solving tests (one long clinical case) and grant viva (oral) was significantly less in group-II(table-I). Conclusion: The objectivity of questions prefers over short essay questions by students as they scores well in theory as well as in practical exams , while they poorly performed in clinical exam (the assessment of higher cognitive functions). The objectivity may eliminate the subjective difference in conventional type of evaluation. Asian Journal of Medical Sciences Vol.8(1) 2017 82-84